The Role of Osteokines in Sarcopenia: Therapeutic Directions and Application Prospects - Lu, Wenhao; Xiao, Wenfeng; Xie, Wenqing; Fu, Xin; Pan, Linyuan; Jin, Hongfu; Yu, Yongle; Zhang, Yi; Li, Yusheng (Frontiers in Cell and Developmental Biology, 2021)
Sarcopenia is an age-related disease in which muscle mass, strength and function may decline with age or can be secondary to cachexia or malnutrition and can lead to weakness, falls and even death. With the increase in life expectancy, sarcopenia has become a major threat to the health of the elderly. Currently, our understanding of bone-muscle interactions is not limited to their mechanical coupling. Bone and muscle have been identified as secretory endocrine organs, and their interaction may affect the function of each. Both muscle-derived factors and osteokines can play a role in regulating muscle and bone metabolism via autocrine, paracrine and endocrine mechanisms. Herein, we comprehensively summarize the latest research progress on the effects of the osteokines FGF-23, IGF-1, RANKL and osteocalcin on muscle to explore whether these cytokines can be utilized to treat and prevent sarcopenia.